Evaluation of Eribulin Combined with Irinotecan for Treatment of Pediatric Cancer Xenografts - Robles, Andrew J.; Kurmasheva, Raushan T.; Bandyopadhyay, Abhik; Phelps, Doris A.; Erickson, Stephen W.; Lai, Zhao; Kurmashev, Dias; Chen, Yidong; Smith, Malcom A.; Houghton, Peter J. (Clinical cancer research, 2020)
Vincristine combined with camptothecin derivatives showed synergy in preclinical pediatric cancer models, and the combinations are effective in treatment of childhood solid tumors. We determined whether the synergy between vincristine and irinotecan extends to eribulin, another microtubule inhibitor. Vincristine or eribulin, alone or combined with irinotecan, was studied in 12 xenograft models. Tumor regression and time to event were used to assess antitumor activity. Pharmacodynamic studies and RNA sequencing (RNA-seq) were conducted 24 and 144 hours after single-agent or combination treatment. Effects on vascular development were studied in Matrigel plugs implanted in mice. The interaction between binary combinations was examined . Eribulin combined with irinotecan was more effective than vincristine-irinotecan in 6 of 12 models. Pharmacodynamic markers induced by eribulin (phospho-histone H3) and irinotecan (γ-H2A.X) were abrogated in combination-treated tumors. The predominant RNA-seq signature in combination-treated tumors was activation of the TP53 pathway with increased nuclear TP53. Massive apoptosis was observed 24 hours only after treatment with the eribulin combination. , neither combination showed interaction using combination index analysis. Eribulin alone and the combination caused alterations in developing vasculature. The eribulin combination is very active in these xenograft models, but not synergistic . The combination reduced pharmacodynamic markers indicative of single-agent mechanisms but in tumors, dramatically activated the TP53 pathway. Although a mechanism for synergy requires further study, it is possible that eribulin-induced inhibition of microtubule dynamics enhances irinotecan-induced nuclear accumulation of TP53, leading to rapid cell death.